2013
DOI: 10.1089/ars.2012.4892
|View full text |Cite
|
Sign up to set email alerts
|

Is Inflammation a Mitochondrial Dysfunction-Dependent Event in Fibromyalgia?

Abstract: Fibromyalgia (FM) is a complex disorder that affects up to 5% of the general population worldwide. Both mitochondrial dysfunction and inflammation have been implicated in the pathophysiology of FM. We have investigated the possible relationship between mitochondrial dysfunction, oxidative stress, and inflammation in FM. We studied 30 women diagnosed with FM and 20 healthy women. Blood mononuclear cells (BMCs) from FM patients showed reduced level of coenzyme Q₁₀ (CoQ₁₀) and mtDNA contents and high level of mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 10 publications
(22 reference statements)
2
71
0
2
Order By: Relevance
“…However, there are indications that mitochondrial dysfunction induced by CoQ10 deficiency is associated with inflammasome activation and production of IL-1β and IL-18 both in vitro and in vivo, including higher serum levels of both of these cytokines in FMS patients compared to healthy controls [435]. Serum TNFα concentrations were also elevated and the levels of IL-1β and TNFα correlated with pain scores [418]. The concentrations of CoQ10 in PBMC closely parallel those in skeletal muscle [499].…”
Section: Muscle Abnormalitiesmentioning
confidence: 84%
See 2 more Smart Citations
“…However, there are indications that mitochondrial dysfunction induced by CoQ10 deficiency is associated with inflammasome activation and production of IL-1β and IL-18 both in vitro and in vivo, including higher serum levels of both of these cytokines in FMS patients compared to healthy controls [435]. Serum TNFα concentrations were also elevated and the levels of IL-1β and TNFα correlated with pain scores [418]. The concentrations of CoQ10 in PBMC closely parallel those in skeletal muscle [499].…”
Section: Muscle Abnormalitiesmentioning
confidence: 84%
“…Instead, the available data are highly heterogeneous. For example, higher, lower, or similar group mean concentrations of IL-1β, IL-6, and TNFα have been reported in FMS patients compared to healthy controls [340,[416][417][418][419][420][421][422][423][424]. Fewer studies have addressed the peripheral levels of Th2 or anti-inflammatory cytokines, but the results have also been quite varied, with mean serum or plasma levels of IL-4, IL-5, and IL-10 being increased, decreased, or not significantly different between FMS patients and healthy controls [416,417,[425][426][427].…”
Section: Cytokinesmentioning
confidence: 85%
See 1 more Smart Citation
“…In particular, patients with FMS demonstrated higher serum prolidase activity, total oxidative status, and oxidative stress index than healthy controls, and serum prolidase activity positively correlated with pain and fatigue scores (Bozkurt et al, 2014). Moreover, PBMCs from FMS patients showed reduced levels of coenzyme Q 10 (CoQ 10 ) and mtDNA contents, but high levels of mt reactive oxygen species and serum TNF (Cordero et al, 2013). Oxidative stress is present during tissue inflammation and also triggers MCs (Frossi et al, 2003).…”
Section: Pathogenesismentioning
confidence: 99%
“…Recent studies have revealed that mitochondrial dysfunction plays a key role in the inflammatory response (Cordero et al, 2013;Joven, 2013). To investigate the effect of LL-37 on mitochondrial function, the protein levels of peroxisome proliferator-activated receptor gamma coactivator-1 ␣ (PGC-1␣), the key regulator of mitochondrial biogenesis, and mitochondrial respiratory chain enzyme complexes were determined in LL-37 overexpressing and knockdown cells.…”
Section: Ll-37 Increases Mitochondrial Function and Regulates Mitochomentioning
confidence: 99%